Probing cytochrome P450 (CYP) bioactivation with chloromethylindoline bioprecursors derived from the duocarmycin family of compounds. (15th June 2021) - Ortuzar, Natalia; Karu, Kersti; Presa, Daniela; Morais, Goreti R.; Sheldrake, Helen M.; Shnyder, Steve D.; Barnieh, Francis M.; Loadman, Paul M.; Patterson, Laurence H.; Pors, Klaus; Searcey, Mark
Graphical abstract: Abstract: The duocarmycins belong to a class of agent which has great potential for use in cancer therapy. Their exquisite potency means they are too toxic for systemic use, and targeted approaches are required to unlock their clinical potential. In this study, we have explored seco-OH-chloromethylindoline (CI) duocarmycin-based bioprecursors for their potential for cytochrome P450 (CYP)-mediated cancer cell kill. We report on synthetic and biological explorations of racemic seco-CI-MI, where MI is a 5-methoxy indole motif, and dehydroxylated analogues. We show up to a 10-fold bioactivation of de-OH CI-MI and a fluoro bioprecursor analogue in CYP1A1-transfected cells. Using CYP bactosomes, we also demonstrate that CYP1A2 but not CYP1B1 or CYP3A4 has propensity for potentiating these compounds, indicating preference for CYP1A bioactivation.